2013
DOI: 10.1128/jb.02166-12
|View full text |Cite
|
Sign up to set email alerts
|

Coordination of FocA and Pyruvate Formate-Lyase Synthesis in Escherichia coli Demonstrates Preferential Translocation of Formate over Other Mixed-Acid Fermentation Products

Abstract: Enterobacteria such as Escherichia coli generate formate, lactate, acetate, and succinate as major acidic fermentation products. Accumulation of these products in the cytoplasm would lead to uncoupling of the membrane potential, and therefore they must be either metabolized rapidly or exported from the cell. E. coli has three membrane-localized formate dehydrogenases (FDHs) that oxidize formate. Two of these have their respective active sites facing the periplasm, and the other is in the cytoplasm. The bidirec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
63
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 52 publications
(67 citation statements)
references
References 35 publications
4
63
0
Order By: Relevance
“…A similar result was observed with a crude extract derived from anaerobically grown REK702 (Fig. 2a, lane 2), which synthesizes higher levels of both FocA and PflB due to conversion of the focA GUG translation initiation codon to the more efficiently translated AUG codon [1,17]. In contrast, when the experiment was repeated with a crude extract of the pflB mutant RM220, no 85-kDa polypeptide corresponding to PflB was observed (Fig.…”
Section: Resultssupporting
confidence: 75%
See 4 more Smart Citations
“…A similar result was observed with a crude extract derived from anaerobically grown REK702 (Fig. 2a, lane 2), which synthesizes higher levels of both FocA and PflB due to conversion of the focA GUG translation initiation codon to the more efficiently translated AUG codon [1,17]. In contrast, when the experiment was repeated with a crude extract of the pflB mutant RM220, no 85-kDa polypeptide corresponding to PflB was observed (Fig.…”
Section: Resultssupporting
confidence: 75%
“…Recent studies have shown that FocA non-selectively translocates formate and other weak acids in an in vitro system [8], while E. coli cells have a mechanism to transport formate selectively [1,17]. Because PflB is responsible for formate generation in bacteria such as E. coli and its synthesis is tightly coupled with that of FocA, we decided to examine whether PflB in its active or inactive form might exert a regulatory influence on the ability of fermenting E. coli to take up formate.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations